Analysis Of Processing Development Strategy Peanuts In The Village Of Lagadi, District Of Lawa West Muna District - Lestina Lestina; La Rianda; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aimed to determine the strategy for developing peanut processing in Lagadi Village, Lawa District, West Muna Regency. The population in this study were all peanut businesses in Lagadi Village, Lawa District, West Muna Regency, in 2020. Sampling was carried out by "proportional random sampling," i.e., random sampling by considering and paying attention to the proportion of each type from the selection of selected subjects. Done in a balanced way. The sample in this study was three peanut businesses from 9 respondents. The data analysis used is SWOT analysis by first identifying the peanut business's strategic factors (strengths-weaknesses-opportunities-threats). The results in this study are the development strategy of peanut management in Lagadi Village, Lawa District, West Muna Regency, namely, (1) farmers optimize land use with experienced workers. (2) the need for the role of extension workers in developing peanut management businesses. (3) the need for the role of the government and the owners of capital in procuring superior seeds. and (4) farmers carry out pest control with pesticides by utilizing capital from the owner of the capital.